2019
DOI: 10.1111/jnc.14897
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gradients of various neurotransmitter markers in caudate nucleus and putamen of the human brain

Abstract: The caudate nucleus (CN) and the putamen (PUT) as parts of the human striatum are distinguished by a marked heterogeneity in functional, anatomical, and neurochemical patterns. Our study aimed to document in detail the regional diversity in the distribution of dopamine (DA), serotonin, γ‐aminobuturic acid, and choline acetyltransferase within the CN and PUT. For this purpose we dissected the CN as well as the PUT of 12 post‐mortem brains of human subjects with no evidence of neurological and psychiatric disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…It is noteworthy that, upon intra-nigral administration, the animals did not exhibit classical signs of experimental parkinsonism, except for the loss of motor coordination and the higher pain sensitivity [ 15 ]. The pattern of striatal DA depletion we report after FPN, mostly medial, does not correspond to the pattern of destruction in Parkinson’s disease, mostly lateral [ 72 ]. However, DA neurons are altered, with profound changes in the correlative pattern of monoamine markers across the brain, which could make our study interesting for the prodromal, pre-symptomatic phase of Parkinson’s disease or Huntington’s disease.…”
Section: Discussionmentioning
confidence: 98%
“…It is noteworthy that, upon intra-nigral administration, the animals did not exhibit classical signs of experimental parkinsonism, except for the loss of motor coordination and the higher pain sensitivity [ 15 ]. The pattern of striatal DA depletion we report after FPN, mostly medial, does not correspond to the pattern of destruction in Parkinson’s disease, mostly lateral [ 72 ]. However, DA neurons are altered, with profound changes in the correlative pattern of monoamine markers across the brain, which could make our study interesting for the prodromal, pre-symptomatic phase of Parkinson’s disease or Huntington’s disease.…”
Section: Discussionmentioning
confidence: 98%
“…The bilateral thalamus is a susceptible target of ANE related to late immune demyelination in COVID-19 (5) and also brain regions sensitive to hypoxemia. The caudate and putamen as parts of the human striatum are distinguished by a marked heterogeneity in functional, anatomical, and neurochemical patterns (21). For CBF comparisons, the SG showed more widespread CBF decrease in the subcortical nuclei mainly located in the striatum and amygdala compared to the MG.…”
Section: Subcortical Abnormalitymentioning
confidence: 98%
“…Numerous studies have revealed the presence of anatomical and biochemical heterogeneity across these regions that underlie functional endpoints and represent challenges to elucidating the neurochemistry, behavior, and pathologies associated with these regions. In this volume of the Journal of Neurochemistry , Hörtnagl, Pifl, Hörtnagl, Reiner, and Sperk () provide an original study that reports the presence of regional heterogeneity in levels of several neurotransmitters, metabolites, or synthetic enymes within the caudate nucleus and putamen of deceased humans with no neurological or psychiatric antecedent. A major focus of the study was devoted to dopamine (DA) and its metabolites homovanillic acid (HVA) and 3,4‐dihydroxyphenyl acetic acid (DOPAC), but analysis was also performed for serotonin (5‐HT) and its metabolite 5‐hydroxyindoleacetic acid (5‐HIAA), gamma‐aminobutyric acid (GABA), and activity of choline acetyl transferase (ChaT) as a marker for acetylcholine.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, this approach confers the potential to quantify multiple neurotransmitters and metabolites across the CNS and subterritories of specific brain regions [see for instance the publication of one of the authors (Pifl, Schingnitz, & Hornykiewicz, )], permitting the assessment of neurotransmitter systems in different conditions (Rezai Amin et al, ) and between individuals in distinct cohorts (Dellu‐Hagedorn, Rivalan, Fitoussi, & Deurwaerdere, ; Schepisi et al, ). Here Hörtnagl et al () show that these values can be determined with anatomical precision and permit elucidation of potential relationships between pairs of brain regions that could uncover unsuspected information on functional organization. These approaches may be leveraged in future studies to elucidate new aspects of neuronal activity and to address inter‐individual differences contributing to the complex partnership between homologous and heterologous regulation of terminal function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation